(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This analytical article examines the mechanisms of water–electrolyte imbalance among road-patrol service (RPS) officers working outdoors under conditions of high ambient temperature and intense solar radiation. The study is based on international scientific publications from 2020–2024, data from global health and occupational safety organizations, and meta-analyses of observational studies involving 118–160 personnel working in hot climate conditions.